Diagnostic Accuracy of Rapid Assessment of Avoidable Blindness: A Population-based Assessment - Zhang, Xiu Juan; Leung, Christopher K.S.; Li, Emmy Y.; Musch, David C.; Zheng, Chong Ren; He, Ming Guang; Chang, David F.; Lam, Dennis S.C. (American journal of ophthalmology, 2020)
To evaluate the diagnostic accuracy of rapid assessment of avoidable blindness (RAAB). Population-based diagnostic accuracy study. A total of 2145 (95.3%, 2145/2250) subjects aged 50 years and older who participated in the RAAB survey were included. All the recruited participants underwent ophthalmic examination according to the RAAB protocol and then were reexamined with instruments in a mobile eye clinic set up in a village center on the same day. Examination in the mobile clinic included standardized visual acuity (VA) tests using logMAR charts, refraction, slit-lamp biomicroscopy, and dilated fundal examination with a binocular indirect ophthalmoscope. Blindness and economic blindness were defined as VA in the better-seeing eye <3/60 and <6/60, respectively. Visual impairment (VI) was defined as VA <6/18 in the better eye. The primary cause of blindness and VI was defined according to the cause of VI in the participant's better eye. Main Outcome Measures: The sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and area under the curve (AUC) of receiver operating characteristics of RAAB for detection of blindness and the principal causes of VI. A total of 1816 subjects (84.7%), including 686 men (37.8%) and 1130 women (62.2%), underwent ophthalmic examination in the mobile eye clinic. The mean (±standard deviation) age was 64.4 ± 9.6 years. The sensitivities, specificities, AUC, PLR, and NLR of RAAB were 90.3%, 99.3%, 0.948, 124.0, and 0.10, respectively, for detection of blindness (presenting visual acuity, PVA <3/60); 89.5%, 98.7%, 0.940, 69.2, and 0.11, respectively, for detection of economic blindness (PVA <6/60); and 90.3%, 97.7%, 0.940, 38.7, and 0.10, respectively, for detection of VI (PVA <6/18). The sensitivities, specificities, AUC, PLR, and NLR were 90.5%, 98.1%, 0.943, 48.1, and 0.10; and 60.4%, 98.7%, 0.796, 46.4, and 0.40 for detection of VI (PVA <6/18) owing to cataract and refractive error, respectively. The diagnostic performances of RAAB were high for detecting the prevalence of blindness, VI, and VI owing to cataract.